Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper investigates impact of financial technology (FinTech) on Malaysia's financial sector. Malaysia is digitally enabled to seize the opportunities brought by FinTech. Malaysian banks continue to dominate in deposits, lending and capital raising, but they have been gradually reducing their emphasis on physical distribution networks. The top five Malaysian banks have increased their technology-related spending over the past three years. Regulators have been mindful of developments outside of the traditional regulatory perimeter that could pose financial stability risks. Rapidly evolving technology is likely to bring multiple challenges to the financial sector. Regulatory requirements are an important component of operating in the FinTech space. Regulators must strike a balance between ensuring financial stability and consumer protection, while promoting innovation and competition. In order to address the lack of regulatory acumen among FinTech industry players, Bank Negara Malaysia has spearheaded various initiatives. A key challenge for Malaysian regulators is to strike a balance between reaping the benefits of FinTech and mitigating potential downside risks in both conventional and Islamic finance. Frequent refinements to regulations and supervision are required to keep pace with the highly dynamic nature of FinTech to balance benefits and risks.